(untitled) (Philological Studies, 2022)
In this paper, we shall address the issue of pseudonymity in Macedonian literature. We shall focus on the process of collecting, analyzing, and synthesizing unsigned works or those signed with hidden names, initials, graphic signs, etc. We categorize them into several groups (cryptonyms, collective pseudonyms, geonyms or troponyms, latinisms, phytonyms, etc). We shall present these observations as an example of the possibilities for further research in the field of pseudonymy, as well as the need to clarify the necessities and the ways to write under a hidden name. We consider this work as a relevant basis for providing insight into the complexity of the issue of Macedonian literary pseudonyms.